To Compare the Efficacy of Platelet-Rich Plasma with Low-Level Laser Therapy and Low-Level Laser Therapy Alone in the Treatment of Chronic Plantar Fasciitis - Sushil Kumar Saini; Atul Kumar Saroj; Ashutosh Verma (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Increased body weight, repeated micro trauma and work on hard surfaces are the risk factors for plantar fasciitis. Platelet rich plasma (PRP) can be injected to various tissues where it releases high amounts of platelet derived growth factors that increases growth and healing process. Low level laser therapy (LLLT) is an alternative treatment that uses low power lasers. Potential benefits in reducing the pain and spasm. Methodology: Patients between 18 to 60 years were included in this prospective randomized controlled trial. Diagnosis made mainly on clinical grounds. We divided our patients in two groups randomly using simple number random method. GROUP-A patients treated with PRP along with laser therapy. GROUP-B treated with laser therapy only. We used visual analogue scale (VAS) and foot and ankle disability (FAD) index for assessment of pain relief during follow up. Results: 88 patients were included in this study. The VAS score was significantly (P<0.05) become lower in Group A patients as compared with Group B and significant increase in FAD index (P<0.01) among the Group A patients as compare to Group B from prior to infiltration and at follow up. Conclusion: In these patients local infiltration with platelet rich plasma has yielded good results. Low level light therapy also can be used for treating planter fasciitis, but better result found when it given together.